Modeling the Ranking of Tourist Destinations in West Kalimantan Using the Fuzzy Analytical Hierarchy Process (FAHP) Approach - Rama Valivi; Nilamsari Kusumastuti; Yudhi Yudhi; Bayu Prihandono (Universitas Ma'arif Lampung, 2025)
The selection of tourist destinations in West Kalimantan that meet tourist’s needs is a challenge for tourists, due to lack of information and involves various criteria that are subjective and uncertain. An analytical method is needed to evaluate and rank tourist destinations in West Kalimantan. This research aims to rank tourist destinations in West Kalimantan so that it can become an information tool for tourists. The Fuzzy Analytical Hierarchy Process (FAHP) is a multi-criteria decision-making method that combines the Analytical Hierarchy Process (AHP) with fuzzy logic concepts to overcome uncertainty and improve assessment accuracy. The FAHP is used in ranking cascade tourist destinations by determine the criteria (C) used in choosing tourist destinations, namely natural beauty, uniqueness of natural resources, accessibility, supporting facilities, safety and comfort, potential activities, popularity and reputation, and affordability. Furthermore, the research questionnaire was prepared based on the criteria. From the results of distributing research questionnaires, it can be determined that cascade tourism destinations are used as alternatives (A), namely Riam Jugan, Pangar, Ampakng, Mangoi, Batu Susun, Marum, Berawat'n, Parangek, Merasap, and Eria. Next, the calculation of the weight for each criterion (W) is carried out. After that, the weight matrix of each cascade tour is calculated against each criterion (X) and the preference value (Y) for each cascade tourist destination. The result of applying the FAHP method is the ranking of cascade tourist destinations based on the order of preference value (Y) from higher to lower.